Regulation of phenolic secondary metabolites production by Echinacea purpurea L. Moench callus culture of root origin - Ditchenko, Tatyana I.; Yurin, Vladimir M. (Experimental Biology and Biotechnology, 2019)
The protocol for obtaining a callus culture of purple coneflower (Echinacea purpurea L. Moench) of root origin from aseptically grown seedlings as a source of explants has been developed. To optimize the growth of callus culture biomass 10 combinations of synthetic auxins (2,4-D, NAA) and cytokinins (kinetin, BAP) have been tested. The levels of hydroxycinnamic acid and flavonoid accumulation in callus, cultivated in the presence of different combinations of phytohormones, are determined. It has been established that modification of the mineral base of the Murashige – Skoog (MS) nutrient medium (reduction of nitrate and phosphate concentration, complete exclusion of ammonium) makes it possible to significantly increase the content of a target secondary metabolites. It was shown that there is no stimulating effect of sucrose on the levels of phenylpropanoid and flavonoid accumulation.